Poly[[(μ2-di-3-pyridylmethanone-κ2N:N′)(μ2-hexafluorosilicato-κ2F:F′)copper(II)] dihydrate] - Yong-Li Yang (Acta Crystallographica Section E, 2012)
In the title complex, {[Cu(SiF6)(C11H8N2O)2]·2H2O}n, the CuII atom adopts an N4F2-octahedral coordination geometry with four pyridine N atoms in the equatorial sites and two F atoms in the axial sites. The di-3-pyridylmethanone and hexafluorosilicate ligands act as bidentate ligands, linking symmetry-related CuII atoms. Water molecules form O—H...O and O—H...F hydrogen bonds with the di-3-pyridylmethanone and hexafluorosilicate ligands. The Cu2+ and SiF62− ions are each located on a twofold axis.